Knowledge, attitudes and perceptions of workers on safety hazards and health risks in vehicle body manufacturing companies in Nairobi County, Kenya - Abanga, Charles; Moturi, Wilkister; Makindi, Stanley (IJRISS, 2024)
The manufacturing of vehicle bodies in Nairobi County, Kenya, exposes workers to a number of safety and health risks. For the purpose of creating efficient safety and health programs, it is essential to comprehend the knowledge, attitudes, and perceptions of employees about these hazards. Therefore, this paper intended to investigate the knowledge, attitudes, and perceptions of employees regarding health and safety hazards in Nairobi County, Kenya where majority of vehicle body manufacturing companies are situated. A structured questionnaire was used to obtain qualitative and quantitative data from 260 firms using a cross-sectional survey approach. The data was analyzed using descriptive and inferential statistics. The results showed that the knowledge, attitudes and perception of workers on safety hazards and risks in the vehicle body manufacturing companies was highly affected and dependent on the need for occupational health risks and safety hazards being reported to the administration. Within this, majority respondents argued that improved personnel management would be essential in improving knowledge, attitudes and perception of workers on the OSH. The results will provide insight into the level of workers’ awareness of health and safety problems, their attitudes toward safety precautions, and their opinions of how effective current safety programs are. These findings will help to establish targeted safety measures and policies that will lessen the impact of health and safety concerns on workers in Nairobi County, Kenya’s vehicle body manufacturing sector.
Keywords: Knowledge, Attitudes, Perception, Vehicle Body Manufacturing